Analysis of customer perception of product attributes in pet food: implications for marketing and product strategy - Hobbs, Lonnie Jr. (Kansas State University, 2019)
The pet food industry continues to grow driven by higher disposable income and increased popularity of pet ownership among millennials. Research shows that pet food sales increased by 27% from $59.3 billion in 2010 to $75.25 billion in 2016. The increase in demand is accompanied by growing preference for specialized product attributes such as natural, organic, and many other premium product attributes. Research shows that many pet food trends today mimic human food trends as there is a growing tendency among pet owners to humanize their pets. These trends have forced companies to re-evaluate their production and marketing strategies in order to take advantage of the profit potential. They have begun using product differentiation based on various intrinsic attributes (e.g. color, texture, smell, appearance, etc…) and extrinsic attributes (e.g. brand, denomination of origin, image, etc…). As companies aim to accommodate the increasing specialized demands of consumers, they must be aware of consumer’s perception of value associated with different product attributes. The ability of the companies to accurately analyze and interpret consumer value perceptions and expectations is crucial for successfully capturing and maintaining market share in expanding specialty pet food categories. There is emerging literature in this area examining customer preferences and willingness to pay for specific attributes of pet food. However, the extent of this literature is limited by the availability and quality of consumer data. Recent advancements in information and communication technologies combined with the growing trend of online shopping in general and pet food in particular have generated new data source and provided opportunity for analysis of consumer perceptions. The online pet food and supplies purchases in the U.S. have increased by 58% from $1.18 billion in 2011 to 1.86 billion in 2015. Studies in other areas such as human food, health, services, banking, and many other markets have used online review data to study consumer preferences. However, there are no such studies in pet food. The growth in pet food and increasing profit potential combined with increased online shopping provides a good opportunity for research in this area. The purpose of this thesis is to provide insight on consumer perception of pet food product attributes. Specific objectives include identifying major emerging consumer trends in pet food, examine strategies used by pet food in designing and communicating points of differentiation targeted at emerging consumer trends, analyze consumer perception of the value associated with intrinsic and extrinsic attributes of specialty pet food products. The analysis are based on the data from consumer reviews of online pet food buyers. Websites such as Amazon, Chewy, and Pet Food Direct are used to obtain consumer review, as they are the leading websites for pet food sales. Data on company marketing strategies is obtained from websites and packages of the companies associated with the select specialty pet food brands and product lines. Methods include utilizing the R Studio Statistical software to conduct a content analysis of the consumer reviews. A comparative analysis is performed to examine differences in perception of attributes by customers in different categories based their rating of the product and shopping experience. The primary results showed both companies are primarily marketing the health/benefit characteristics to customers. The results also revealed pet food customers tend to place the most value on health/benefit and ingredient characteristics. The three-circle analysis results showed that each of the attributes and terms marketed by both companies are perceived by customers. This implies that both companies are successfully communicating the value of their products to customers. However, there is potential for both companies to increase their current product positioning strategy to incorporate attributes highlighted as value/needs. The alterations in marketing approach can increase competitive advantage over other companies in the market. The insights generated by this research have a potential to inform marketing, product strategy decisions, and facilitate successful product differentiation by companies in the pet food industry. The methods and the results of this research contribute to the literature in the area of agribusiness and agri-food marketing in general and pet-food marketing in particular, thus it will potentially generate interest among agribusiness scholars and pet-food industry stakeholders.
Keywords: Pet Food; Online Customer Reviews; Product Attributes; Three-Circle Analysis; Product Positioning Strategy; Customer Perceptions